Cubic structures applied to ideals of co-residuated lattices - Yang, Yongwei (IJRDO -JOURNAL OF MATHEMATICS, 2018)
The concept of cubic ideals in co-residuated lattices is introduced and some interesting properties are obtained. Characterization theorem of cubic ideals is also discussed by the notion of cubic level sets. We construct Cartesian product of two cubic ideals by using max-min operations, and give some characterizations of them.